Becoming a dentist: faculty perceptions of student experiences with threshold concepts in a Canadian dental program - Green, Jacqueline; Rasmussen, Kari (Canadian Medical Education Journal, 2018)
Background: In each discipline, there are moments where students “get stuck” in their education and/or training and are often unable to move forward. These moments may be caused by threshold concepts as they represent a portal that students must cross in order to become successful in their chosen profession. This study investigated the threshold concepts from the instructors’ perspective that students must navigate as they transform from learners to dentists within a dental program. Methods: Two focus groups with faculty members within the School of Dentistry, University of Alberta were completed in the fall of 2017. Focus groups explored the faculty’s perception of the students’ transition from learner to dentist, difficult moments in the program, and the students’ ability to navigate the program successfully. Results: A qualitative phenomenographic analysis of the faculty focus group transcripts identified four potential threshold concepts within the dental program: 1) dealing with the whole patient, 2) accountability, 3) that you may not know everything, and 4) problem solving and adapting during practice. Conclusion: This study demonstrates that there are concepts within a dental program that faculty believe students must navigate in order to transition from learner to dentist. These concepts may inform curriculum design as well as other disciplines in the health sciences.